ANALYSIS OF PTKIN OPPORTUNITIES: QUALITY MEASUREMENT THROUGH THE MALCOLM BALDRIGE CRITERIA FOR USING THE WORLD CLASS UNIVERSTY - Ihwan Fauzi (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2021)
This study analyzes the opportunity for PTKIN to reach World Class University using criteria, especially at UIN Sunan Kalijaga Yogyakarta. The quality of an educational institution needs to be continuously improved (continuous improvement) to increase competitiveness. The research used a qualitative approach to the type of case study. Data collection techniques were carried out through; observation, interview and documentation. Furthermore, the research data is presented in a descriptive narrative form. The results of the study show that the accreditation is A (the highest score), but if it is measured or assessed by international standards EdPEx may only get a score in the interval 476 - 575, so that internationally it is categorized as a Good Performance University, yet it has NOT reached the World Class University. Improved by using a new standard to reach a world class university, Malcolm Baldrige is an international standard quality audit that is ready to fight the changing times. Malcolm Baldrige developed a flexible and creative approach in line with the needs of organization, especially the State Islamic Religious College.